(untitled) (Texas Journal of Philology, Culture and History, 2025)
This article investigates the linguo-cultural commonalities and distinctions found in English, Uzbek, and Turkish proverbs, with a focus on core themes such as life, labor, and moral values. By comparing paremias across these three languages, the study highlights how each culture encodes shared human experiences through distinct linguistic forms and metaphorical frameworks. Despite cultural and historical differences, proverbs in all three traditions reflect a common concern with ethical behavior, the dignity of labor, and philosophical reflections on life. The analysis reveals both universal wisdom and culturally specific nuances, illustrating the deep interconnection between language, worldview, and moral education